Genotype x season interaction and characters association in some sesame (Sesamum indicum L.) genotypes under rainfed conditions of Sudan - Balla M. Ahmed, Salah; F. Ahmed, Abubakri (Gezira Journal of Agricultural Science, 2023)
An experiment was carried out at Gedaref Agricultural Research Station, Sudan, during the rainy seasons 2008/09 and 09/2010 to estimate the genotype x season (GxS) interaction and to determine the characters association for seven sesame genotypes. A randomized complete block design with four replicates was used. Data were  collected on days to 50% flowering, days to maturity, plant height, number of capsules/plant, seed yield/plant  and seed yield/ ha.  All characters showed highly significant differences at the genotypic level. The days to 50% flowering and to maturity revealed significant differences in both seasons and the G x S interaction, whereas the seed yield / plant showed significant differences between seasons. Gedaref -1 exceeded the overall mean of seed yield by 26.15%. In both seasons, days to maturity, plant height, number of capsules/plant, seed yield/plant were significantly and positively correlated  at both the genotypic and the phenotypic levels with seed yield /ha and among themselves. It is concluded that sesame yield is highly influenced by the season, and to improve its yield, emphasis should be made on selection of early maturing tall  plants with  more capsules and higher seed yield/plant.